INTERNATIONAL LOGISTICS IN TRANSNATIONAL ECONOMIC RELATIONS: INTEGRATION AND SYSTEM-FORMING ASPECTS - GUPALO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the essence of international logistics within the system of transnational economic relations in the context of the globalization of the world economy. It is demonstrated that globalization processes create a unified economic space, where production processes are integrated, and the role of transnational corporations increases. The importance of international logistics as a key factor in the efficient movement of goods, services, capital, and information is strengthened.The scientific approaches to studying transnational structures and logistics processes, as reflected in the works of domestic and foreign scholars, are analyzed. It is determined that international logistics is interpreted from the perspective of different concepts — functional, strategic, and integrational — which makes it possible to reveal its multidimensional nature in the modern economy. The author’s vision of the essence of international logistics is proposed as a comprehensive process of managing material, information, and financial flows between countries, ensuring the efficient movement of goods, services, and resources within global production and trade systems, and encompassing the planning, organization, control, and optimization of supply chains with consideration of the economic, legal, political, and cultural features of different states, thus promoting the development of international trade and the integration of national economies into the world economy.The theoretical and methodological foundations of international logistics are systematized, which are reflected in the combination of approaches to managing material, information, and financial flows, optimizing global supply chains, and considering the economic, legal, and cultural specifics of various countries. The author presents a conceptual model for integrating international logistics into the system of transnational economic relations, which contributes to adapting global logistics networks to crisis phenomena and reducing the risks of supply disruptions.It is concluded that international logistics has an integrational and system-forming character, as it simultaneously ensures the inclusion of national economies into the global space and forms the structural architectonics of transnational economic relations. This determines its strategic role in strengthening the competitiveness of companies and states, enhancing the efficiency of world markets, and creating the conditions for their sustainable development.
Keywords: international logistics; transnational economic relations; global supply chains; integration; competitiveness; globalization